Assessing the impact of the Asian mussel Arcuatula senhousia in the recently invaded Oristano Lagoon-Gulf system (W Sardinia, Italy). (5th February 2018) - Como, S.; Floris, A.; Pais, A.; Rumolo, P.; Saba, S.; Sprovieri, M.; Magni, P.
Abstract: In the marine environment, the introduction and spread of non-indigenous mussels may cause major modifications to native assemblages and alter the trophic flow within the food web. We analysed the impacts of the recently sighted Asian date mussel Arcuatula (= Musculista ) senhousia on sediment features, native macrozoobenthic assemblages and the δ 13 C and δ 15 N values of dominant macrozoobenthic taxa in the Oristano Lagoon-Gulf system (western Sardinia, Italy). Results showed that the amount of variation generated by the occurrence of Arcuatula senhousia was lower than the intrinsic spatial variability in sediment features, macrozoobenthic assemblages and the δ 13 C values of dominant deposit feeders ( Hediste diversicolor, Cirriphormia tentaculata, Haminoea navicula and Cyclope neritea ) of this system. In addition, δ 13 C and δ 15 N values of A. senhousia were found to be similar to those of co-occurring suspension feeders Cerastoderma glaucum, Ruditapes decussatus and Scrobicularia plana, indicating exploitation of common food resources. The overall lack of effects of A. senhousia may be dependent on the moderate densities encountered in our study area (<1000 individuals m −2 ). We suggest that the low rate of new arrivals, owing to limited shellfish farming and maritime activities in the area, and unfavourable environmental conditions of the lagoons especially in summer (e.g. anoxia) which erode mussel populations, likely prevent A. senhousia from entering its expansion phase and impacting local benthic communities. Highlights: The invasive mussel Arcuatula senhousia was studied in the Oristano Lagoon-Gulf system. No effects were found on the abundance and isotopic composition of local macrofauna. Similar isotopic values of local bivalves and A. senhousia indicate a common diet. Low rate of arrivals and unfavourable environmental conditions impair invasion success.